The importance of using technology in financial operations to further improve banks’ profitability - Hammadi, Huda Abdullah; Mohammed, Assad Munshid (Edelweiss Applied Science and Technology, 2024)
The study aimed to determine the status of technology use and financial operations performance and its impact on profitability indicators. Is there interest in technology among banks and to what extent are banks able to provide advanced services and keep pace with developments? The major developments in modern technology have contributed to the application of modern methods of dealing with customers and banks. These recent changes have made it necessary for Iraqi banks to advance the reality of technology and the performance of financial operations to improve profitability in banks. It has also clarified the importance of using technology and banking services and the role they play in serving customers by taking advantage of these technological developments. This study assumes that the use of technology and the performance of financial operations affect the indicators of banks' profitability. To prove the hypothesis of this study, the data shown by the questionnaire were presented and the sample responses were analyzed regarding the performance of financial operations and enhancing the bank's profitability using technology. Frequency distribution tables for the study variables were prepared and adopted for the purposes of the statistical analysis process to obtain the weighted arithmetic means, standard deviations, and the coefficient of variation, to know the impact of the variables. The study concluded that technological developments have been reflected positively in the banking sector. The researcher concluded the study with a set of suggestions and recommendations to develop and keep pace with technology to increase competition between banks, serve customers, and achieve profitability, including addressing the development of technology.